2014
DOI: 10.1002/jts.21959
|View full text |Cite
|
Sign up to set email alerts
|

From Betrayal to the Bottle: Investigating Possible Pathways From Trauma to Problematic Substance Use

Abstract: Research in both community and clinical settings has found that exposure to cumulative interpersonal trauma predicts substance use problems. Less is known about betrayal as a dimension of trauma exposure that predicts substance use, and about the behavioral and psychological pathways that explain the relation between trauma and substance use. In a sample of 362 young adults, this study evaluated three intervening pathways between betrayal trauma exposure prior to age 18 years and problematic substance use: (a)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 51 publications
(50 reference statements)
2
45
0
Order By: Relevance
“…Research in western contexts has indicated that betrayal trauma, or interpersonal trauma where the individual must rely on the perpetrator for financial or emotional support (e.g. sexual violence from a fishermen with whom the fish trader relies on for financial support), may result in dissociative symptoms as an adaptive mechanism to preserve the relationship for survival [27, 44]. Dissociative symptoms and substance use as numbing mechanisms, while potentially adaptive within the relationship, have adverse consequences for long term functioning [45] and an individual’s ability to discern risk in the environment, increasing HIV sexual risk behavior [24] and risk of re-victimization [27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research in western contexts has indicated that betrayal trauma, or interpersonal trauma where the individual must rely on the perpetrator for financial or emotional support (e.g. sexual violence from a fishermen with whom the fish trader relies on for financial support), may result in dissociative symptoms as an adaptive mechanism to preserve the relationship for survival [27, 44]. Dissociative symptoms and substance use as numbing mechanisms, while potentially adaptive within the relationship, have adverse consequences for long term functioning [45] and an individual’s ability to discern risk in the environment, increasing HIV sexual risk behavior [24] and risk of re-victimization [27].…”
Section: Discussionmentioning
confidence: 99%
“…sexual violence from a fishermen with whom the fish trader relies on for financial support), may result in dissociative symptoms as an adaptive mechanism to preserve the relationship for survival [27, 44]. Dissociative symptoms and substance use as numbing mechanisms, while potentially adaptive within the relationship, have adverse consequences for long term functioning [45] and an individual’s ability to discern risk in the environment, increasing HIV sexual risk behavior [24] and risk of re-victimization [27]. On the other hand, the pathway from non-interpersonal trauma to HIV sexual risk among female fish traders may be less likely to include dissociative symptoms and substance abuse decreasing HIV sexual risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence rate of PTSD in the refugee and asylum seeker populations varies in the literature depending on the population of interest. However, research suggests that refugees are 10 times more likely than the general population to have PTSD and PTSD, depression and substance use have been found to be the most common mental health conditions in populations exposed to mass conflict and displacement (Delker & Freyd, 2014;Fazel, Wheeler, & Danesh, 2005;Steel, 2009). More specifically, researchers have reported various symptoms of PTSD and depression in trauma-exposed refugees, including separation anxiety, worrying, poor concentration, disorientation, flashbacks, nightmares, hypervigilance, violent outbursts, crying, anhedonia, suicide attempts and using substances for coping (Dupont, Kaplan, Verbraeck, Braam, & van de Wijngaart, 2005;Shannon et al, 2015;Tay, Rees, Kareth, & Silove, 2016).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…A growing body of evidence supports the central role that stress plays in engaging in behaviors including substance use and risky sexual activity. In a study among young adults (n = 362), experiencing betrayal trauma prior to age 18 was associated with problematic substance use subsequent to PTSD and difficulty discerning or heeding risk and self-destructiveness (β = 0.07, p < 0.001; β = 0.12, p < 0.001) (Delker and Freyd 2014). PTSD has also been associated with engaging in risky behavior while under the influence of substances (Kingston and Raghavan 2009).…”
mentioning
confidence: 99%